Accumulation Levels of Available Cu and Cu Absorption in Corn in Ultisolss and Alfisolss After the Addition of Fly Ash and Organic Materials - Eko Hanudin; Benito Heru Purwanto; Erin Destri (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2023)
Fly ash was a byproduct of burning coal in thermal power plants that can be used in agriculture as a source of micronutrients. This study aimed to determine the effect of fly ash combined with Biochar and Manure on the chemical properties of the soil, plant growth, and the absorption of Cu corn plants. The study design used a randomized design of factorial groups, with soil type factors namely Alfisols and Ultisols with three repeats. Agronomic observations include plant height, dry weight of roots and headers. Laboratory analysis includes preliminary soil, Fly Ash, Manure, Biochar, soil analysis after harvest, and Cu in leaf. The results showed that the availability of Cu elements in Ultisols was higher by 5.37 mg/kg than Alfisols with an average of 3.90 mg/kg. Cu absorption in maize crops grown in Alfisols soil was greater with an average of 54.7 mg/g when compared to those planted in Ultisols soil by an average of 50.3 mg/g. The treatment between Fly Ash and Manure in a ratio of 1:1 has a tendency to increase Cu absorption with a value of 68 mg/g. Alfisols soil was significantly correlated with organic matter to Cu absorption in Corn plants with a value of R= 0.827. The conclusion of this study was that the availability of Cu elements in Ultisols soil was higher than in Alfisols soil and Cu uptake in corn plants was lower after being treated with the addition of manure and Biochar and corn plant growth was better.